4(u+1)-7=3(u-1)+7

Simple and best practice solution for 4(u+1)-7=3(u-1)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(u+1)-7=3(u-1)+7 equation:


Simplifying
4(u + 1) + -7 = 3(u + -1) + 7

Reorder the terms:
4(1 + u) + -7 = 3(u + -1) + 7
(1 * 4 + u * 4) + -7 = 3(u + -1) + 7
(4 + 4u) + -7 = 3(u + -1) + 7

Reorder the terms:
4 + -7 + 4u = 3(u + -1) + 7

Combine like terms: 4 + -7 = -3
-3 + 4u = 3(u + -1) + 7

Reorder the terms:
-3 + 4u = 3(-1 + u) + 7
-3 + 4u = (-1 * 3 + u * 3) + 7
-3 + 4u = (-3 + 3u) + 7

Reorder the terms:
-3 + 4u = -3 + 7 + 3u

Combine like terms: -3 + 7 = 4
-3 + 4u = 4 + 3u

Solving
-3 + 4u = 4 + 3u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-3u' to each side of the equation.
-3 + 4u + -3u = 4 + 3u + -3u

Combine like terms: 4u + -3u = 1u
-3 + 1u = 4 + 3u + -3u

Combine like terms: 3u + -3u = 0
-3 + 1u = 4 + 0
-3 + 1u = 4

Add '3' to each side of the equation.
-3 + 3 + 1u = 4 + 3

Combine like terms: -3 + 3 = 0
0 + 1u = 4 + 3
1u = 4 + 3

Combine like terms: 4 + 3 = 7
1u = 7

Divide each side by '1'.
u = 7

Simplifying
u = 7

See similar equations:

| -x+3.9forx=-7.2 | | (4x+2)=-34 | | 9+4(-4)+3=-4 | | (4x+2)=34 | | 0.80x+0.20(60)=0.40(78) | | -3.6-7.2=12.7-6.1b | | (4x-2)(4x-2)+(5x)(5x)= | | 10x-4-6x=5x-7 | | (-10)+4=-2(-10)+-6 | | 2a+8=4a+16 | | 5(4x-4)-9=-31 | | 216=8(-5r-3) | | (3x+y*1)=(7*2x-3y) | | 29.95=42-sqrt(0.001x+2) | | (x^2+2xy)dx+xdy=0 | | 5w-6=60 | | 18=9x+4-2x | | (3+2x)=0.5x+1 | | 7x+10=4x-16 | | 3X=6-3 | | -19=v/10 | | 3x+3x-7=47 | | 2x[2+(5+2)]= | | ln(9x)=2ln(2x) | | 5(4x-4)-9=31 | | X-4y+15=0 | | -3x+4x-10=15x+1 | | 3n-2m=mn+4 | | X+7x=-24 | | 5y^2+40y=325 | | 5(3x-7)-3(x+2)-19x= | | 3(x-2)+(-3)=4(x+1) |

Equations solver categories